Melampaui Politik Identitas: Elaborasi Publik dalam Meretas Kemiskinan di Kabupaten Timor Tengah Selatan - Dhavid Kristofel Dira Tome; Yaspis Edgar N. Funay (Universitas Warmadewa, 2021)
This paper will describe and analyze the elaboration of government programs and realities that occur in society as one of the strengths to create a system of integration in the context of poverty in South Central Timor. Furthermore, the article was appointed to show how the identity politics of local communities not only become a symbol of resistance but can also be synergized as a critical space in order to achieve an ideal social transformation. Therefore, the method used in collecting data in the form of reviewing the facts of literature sources will then be tested for relevance to the reality of poverty that is happening in the community. Using Manuel Castells' theory of identity and Peter Blau's explanation of social exchange, this paper will examine the extent to which the incorporation of the values or habits of local communities and government policies can play a role in cracking poverty in the context of South Central Timor. In the end, this paper will also explore the benefits of a mutually beneficial relationship between grassroots residents and the government as a political elite to support economic development and community maturity.